Evaluation of the research career through the citation distribution: An application to the Nobel Prizes in Economics - Dorta-González, Mª Isabel; Dorta-González, Pablo (Revista General de Información y Documentación, 2012)
The citation distribution of a researcher reflects the impact of his production and determines the success of his scientific career. However, it is difficult to apply due to the bidimensional character. Some bibliometric indexes that try to synthesize with a numerical value the principal characteristics of this citation distribution have been proposed recently. In contrast with other bibliometric measures, the biases, that the distribution tails provoke, are eliminated by the h-index. On the other hand, some limitations to discriminate between researchers with different publication habits are presented. This index penalizes to selective researchers, distinguished by the number of citations instead of the number of publications, as compared to great producers. In this work, two original indexes are applied to the evaluation of Nobel Prize winners in Economics.